Ensino de ciências através da promoção da saúde: um estudo contextualizado - ALVES, Darliane de Sousa (Universidade Federal do Oeste do Pará, 2024)
This paper presents a methodological proposal using contextualization, to work on Biological and Chemical concepts, relating them to health with focus on students' daily life. Here is intended to make students aware of the importance of science in their lives. The methodology applied was through one theoretical class and two questionnaires, one applied before and the other appplied after the class. To obtain the results, a statistical analysis of the correct expected answers was made, and also through hypothesis testing, we sought to verify if there was a significant difference in learning. After analising the results was possible to infer that the utilization of the methodology applied was sucerfull, but needs to be adjusted to obtain better results that may contribute to the progress of atual teaching process.